The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1371/journal.ppat.1010350
|View full text |Cite
|
Sign up to set email alerts
|

TBK1 and GABARAP family members suppress Coxsackievirus B infection by limiting viral production and promoting autophagic degradation of viral extracellular vesicles

Abstract: Host-pathogen dynamics are constantly at play during enteroviral infection. Coxsackievirus B (CVB) is a common juvenile enterovirus that infects multiple organs and drives inflammatory diseases including acute pancreatitis and myocarditis. Much like other enteroviruses, CVB is capable of manipulating host machinery to hijack and subvert autophagy for its benefit. We have previously reported that CVB triggers the release of infectious extracellular vesicles (EVs) which originate from autophagosomes. These EVs f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 68 publications
1
3
0
Order By: Relevance
“…Here, we show that PSaV infection in TBK1 deficient porcine cells led to a statistically significant 2.6-fold increase in virus titres. This aligns with observations in studies altering TBK1 levels in both human and murine cells, resulting in a comparable effect on virus proliferation [ 43 , 44 ]. Moreover, the absence of other restriction factors similarly leads to a modest rise in virus titres [ 45 ], underscoring the redundancy of pathways in suppressing viral infection, and highlighting the well-orchestrated defence mechanisms against virus proliferation.…”
Section: Discussionsupporting
confidence: 88%
“…Here, we show that PSaV infection in TBK1 deficient porcine cells led to a statistically significant 2.6-fold increase in virus titres. This aligns with observations in studies altering TBK1 levels in both human and murine cells, resulting in a comparable effect on virus proliferation [ 43 , 44 ]. Moreover, the absence of other restriction factors similarly leads to a modest rise in virus titres [ 45 ], underscoring the redundancy of pathways in suppressing viral infection, and highlighting the well-orchestrated defence mechanisms against virus proliferation.…”
Section: Discussionsupporting
confidence: 88%
“…The role of fission in the production of mitochondrial vesicles was confirmed by inhibition/blocking mitochondrial fission machinery using mitochondrial division inhibitor-1 (Mdivi-1) or direct inhibition of Drp1 with siRNA which resulted in less viral replication and fewer/no virus containing EVs in the culture supernatant ( 48 ). Dr. Sin’s group additionally showed that Tank binding kinase I (TBK1) increased phosphorylation of GABA type A receptor associated protein-like (GABARAPL) proteins leading to EVs that contain mitochondria being released from the cells ( 59 ). CVB3 infection has also been shown to perturb syntaxin-17 facilitated mitophagosome-lysosomal fusion, which may lead to build up and release of formed mitophagosomes from the cell ( 60 ).…”
Section: Mitochondrial Extracellular Vesiclesmentioning
confidence: 99%
“…It turns out that many viruses are known to localize to mitochondria ( 61 64 ), utilize mitochondrial machinery for replication ( 48 , 65 ), evade immune responses within EVs ( 66 ) and modify cellular processes ( 59 , 60 , 67 ). Importantly, most of the viruses that are associated with causing myocarditis [e.g., CVB, influenza, HIV, poliovirus, hepatitis C virus, SARS-CoV-22 ( 68 , 69 )] have been found to target mitochondria to gain a replicative advantage ( 61 64 ) and are ejected from cells/tissues in EVs ( 60 , 65 , 70 , 71 ) suggesting that these mechanisms may provide an explanation for how viruses could cause autoimmune disease.…”
Section: Mitochondrial Autoimmunity and Myocarditismentioning
confidence: 99%
See 1 more Smart Citation